Genetic structure and sex-biased dispersal of a declining cooperative-breeder, the Grey-crowned Babbler, Pomatostomus temporalis, at the southern edge of its range. (1st December 2016) - Stevens, Kate P.; Harrisson, Katherine A.; Clarke, Rohan H.; Cooke, Raylene; Hogan, Fiona E.
Abstract: Loss and fragmentation of habitat can disrupt genetic exchange between populations, which is reflected in changes to the genetic structure of populations. The Grey-crowned Babbler ( Pomatostomus temporalis ) is a cooperatively breeding woodland bird, once common and widespread in south-eastern Australia. The species has suffered population declines of >90% across its southern distribution as a result of loss and fragmentation of habitat. We investigated patterns of genetic diversity and population structure of Grey-crowned Babblers in fragmented habitats at the southernmost extent of its range. We sampled blood from 135 individual Babblers from 39 groups stratified into six subpopulations in three regions. Genotypic data were used to estimate genetic diversity, population substructure, local relatedness and dispersal patterns. Individuals showed high heterozygosity within regions, and varying numbers of private alleles among regions suggested differences in levels of connectivity between regions. Four genetic clusters revealed population substructure consistent with treeless landscapes acting as strong barriers to gene flow. In contrast to previous studies, we identified a male-biased dispersal pattern and significant isolation-by-distance patterns for females at fine spatial scales. We recommend that conservation plans for this species incorporate opportunities to increase and enhance corridor areas to facilitate genetic exchange among subpopulations.